2017
DOI: 10.1002/cnma.201700038
|View full text |Cite
|
Sign up to set email alerts
|

From Trash to Treasure: Turning Air Pollutants into Materials for Energy Storage

Abstract: Environmental and energy issues are hot topicsi n the sustainable development of our planet. Air pollution, as av ital environmental issue, has puzzled us for decades, and ag reen and economical approacht oc ontrol air pollutantsi s urgently required. New energy-storage techniques have emerged as fascinating routes to reduce potentiale nvironmental problems. Therefore, the combination of air pollutants with energy-storage devices is an appealings olution for air pollution.H erein, the principles of recovering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Sulfur oxides (SO x ), a common air pollutant originated from the combustion of sulfur compounds in fossil fuels, is the main cause of acid rain. Excessive emission of SO x will destroy the ecological environment system and accelerate the corrosion of metals [1][2][3]. Therefore, to reduce the harm of SO x to the global environment, researchers are trying to nd an advanced technology to achieve ultra-deep desulfurization of transportation fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur oxides (SO x ), a common air pollutant originated from the combustion of sulfur compounds in fossil fuels, is the main cause of acid rain. Excessive emission of SO x will destroy the ecological environment system and accelerate the corrosion of metals [1][2][3]. Therefore, to reduce the harm of SO x to the global environment, researchers are trying to nd an advanced technology to achieve ultra-deep desulfurization of transportation fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies have reported that the combination of air pollutants with EES devices is an appealing approach for both controlling environmental pollution and storing energy [21]. Most air pollutants are oxidative, suggesting the possibility of their being recycled in an EES device.…”
Section: Introductionmentioning
confidence: 99%
“…"Others" in Figure 13 correspond to gas purification process streams (natural gas [138] and biogas [139]), preparation of synthetic gaseous mixtures [140] and residual agroforestry process streams [141]. Capture of CO 2 from the atmosphere was mentioned by 8% of the review papers that specified the analyzed carbon sources [142][143][144][145][146][147][148][149][150][151][152][153][154].…”
mentioning
confidence: 99%